Clinical and Radiographical Study Regarding Treatment of Incipient Carious Lesions with Icon Infiltration Method - Galina Pancu; Mariana Ilie; Sorin Andrian; Geanina Iovan; Claudiu Topoliceanu; Ion Pancu; Angela Gheorghe; Antonia Moldovanu; Simona Stoleriu (Romanian Society of Oral Rehabilitation, 2012)
The treatment of incipient carious lesions using ICON method can be considered an innovative orientation of modern dentistry, based on principle of Minimal Invasive Therapy (1, 2). Aim The aim of this study is to assess the ability of ICON method to stop the evolution of incipient carious lesions on smooth surfaces of molar I and the possibility to treat aesthetic deficiencies (white-spot and brown-spot). Material and methods The study group included 14 patients presenting 19 uncavitated incipient carious lesions to the level of smooth surfaces (buccal, oral, mesial, distal) of molars I (scores ICDAS 1, 2, radiographic score E1, E2, D1). The affected enamel surfaces were submitted to ICON therapy, after cleaning and isolation. The clinical and radiographic assessment of incipient caries evolution was processed on a time interval of 12 months. Results The stopping of carious processes evolution is obtained in 89.48% cases. Conclusions The ICON method is noninvasive and can completely stop the evolution of carious enamel lesions in stages E1 and E2.